Effects of age and obesity on trunk kinetics and kinematics during dominant side one-handed carrying. (20th September 2019) - Badawy, Mohamed; Schall, Mark C.; Zabala, Michael E.; Coker, Jordan; Sesek, Richard F.; Gallagher, Sean; Davis, Gerard A.
Abstract: The proportions of older and obese people are increasing in both the general and working populations worldwide. Older and obese individuals are more susceptible to work-related musculoskeletal disorders (MSDs) in comparison with healthy, younger individuals. Manual material handling (MMH) is associated with the development of work-related MSDs. Although previous research has suggested that one-handed carrying is a particularly undesirable method of MMH, the effects of one-handed carrying on trunk kinetics and kinematics among older and/or obese people have not been adequately studied. The objective of this study was to examine the effects of age and obesity on trunk angles and moments during dominant side one-handed carrying of various load magnitudes. Twenty (20) participants divided into four groups with respect to age (young and older) and obesity (obese and non-obese) carried different loads ( No-load [0 kg], Light [5.67 kg], and Heavy [10.21 kg]) in their dominant hand for approximately 6 m. Three-dimensional (3D) trunk angles and moments approximately about the L4/L5 vertebral segment were calculated using Visual3D. The findings indicated that while carrying a load in the dominant hand plays an important role in changing trunk kinematics and kinetics, the results were not dependent on age and/or obesity category. Absolute moments were greatest among participants in the obese groups; however, these moments were mitigated when normalized to body weight and height (%BW * Ht). Age did not exacerbate the effects of load magnitude on trunk kinetics and kinematics.